2016
DOI: 10.3747/pdi.2015.00182
|View full text |Cite
|
Sign up to set email alerts
|

Older Age, Higher Body Mass Index and Inflammation Increase the Risk for New-Onset Diabetes and Impaired Glucose Tolerance in Patients on Peritoneal Dialysis?

Abstract: N ew-onset diabetes and impaired glucose tolerance (IGT) have been shown to be associated with increased cardiovascular events and risk of death in the general population (1-3) and in patients undergoing dialysis (4-7). Since new-onset diabetes and IGT (NODI) is a common complication among patients on dialysis (4)(5)(6)8), it is important to explore the potential risk factors for this complication. However, published data on this issue are limited in dialysis populations.To our knowledge, traditional risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
3
20
2
1
Order By: Relevance
“…In the study by Dong et al advanced age was associated with increased risk of NODM in PD patients (21). Furthermore, in other clinical studies NODM in dialysis patients was linked with higher age (4,10,22).…”
Section: Other Possible Risk Factors For Nodm In Pd and Hd Patientsmentioning
confidence: 87%
See 3 more Smart Citations
“…In the study by Dong et al advanced age was associated with increased risk of NODM in PD patients (21). Furthermore, in other clinical studies NODM in dialysis patients was linked with higher age (4,10,22).…”
Section: Other Possible Risk Factors For Nodm In Pd and Hd Patientsmentioning
confidence: 87%
“…Additionally, Szeto et al confirmed that FPG‐levels also significantly correlated with the age of PD patients . In two clinical studies obesity appeared to be an essential risk factor for new‐onset hyperglycemia in PD patients, which however, is in contrast to the study cohort of Szeto et al . Chronic inflammation is associated with NODM in both PD and HD patients.…”
Section: Diagnosis Of Nodm In Pd Patientsmentioning
confidence: 93%
See 2 more Smart Citations
“…Az aktív peritonealis dialízis mellett kialakuló szénhidráttolerancia-zavar (IGT vagy új diabetes) fokozott monitorozást igényel. A nóvum diabetes -egyes megfigyelések szerint -a kezdeti nagyobb BMI-vel, az inflammatorikus folyamatok aktivációjával (hsCRP) és az idősebb életkorral voltak kapcsolatba hozhatók [38].…”
Section: A Bőr-autofluoreszcencia Méréseunclassified